3D bioprinting of gellan gum‐based hydrogels tethered with laminin‐derived peptides for improved cellular behavior. Issue 10 (9th June 2022) - Alheib, Omar; da Silva, Lucilia P.; Youn, Yun Hee; Kwon, Il Keun; Reis, Rui L.; Correlo, Vitor M.
Abstract: The treatment of skeletal muscle defects is still a topic of noteworthy concern since surgical intervention is not capable of recovering muscle function. Herein, we propose myoblasts laden in laminin‐inspired biofunctionalized gellan gum hydrogels as promising tissue‐engineered skeletal muscle surrogates. Gellan gum‐based hydrogels were developed by combining native gellan gum (GG) and GG tethered with laminin‐derived peptides (CIKVAVS (V), KNRLTIELEVRTC (T) or RKRLQVQLSIRTC (Q)), using different polymer content (0.75%–1.875%). Hydrogels were characterized in terms of compressive modulus, molecules trafficking, and C2C12 adhesion. Hydrogels with higher polymeric content (1.125%–1.875%) showed higher stiffness whereas hydrogels with lower polymer content (0.75%–1.125%) showed higher fluorescein isothiocyanate‐dextran molecules diffusion. Cell spreading was achieved regardless of the laminin‐derived peptide but preferred in hydrogels with higher polymer content (1.125%–1.875%). Taken together, hydrogels with 1.125% of polymer content were selected for printability analysis. GG‐based inks showed a non‐newtonian, shear‐thinning, and thixotropic behavior suitable for printing. Accordingly, all inks were printable, but inks tethered with T and Q peptides presented some signs of clogging. Cell viability was affected after printing but increased after 7 days of culture. After 7 days, cells were spreading but not showing significant signs of cell–cell communications. Therefore, cell density was increased, thus, myocytes loaded in V‐tethered GG‐based inks showed higher cell–cell communication, spreading morphology, and alignment 7, 14 days post‐printing. Overall, myoblasts laden in laminin‐inspired biofunctionalized GG‐based hydrogels are a promising skeletal muscle surrogate with the potential to be used as in vitro model or explored for further in vivo applications.